Treatment of social cognition impairments in patients with traumatic brain injury: a critical review. (2nd January 2019) - Vallat-Azouvi, Claire; Azouvi, Philippe; Le-Bornec, Gaelle; Brunet-Gouet, Eric
ABSTRACT: Objective : The aim of this study is to review published research on treatment of social cognition impairments in patients with traumatic brain injury (TBI). Methods : Following the PRISMA guidelines, a PubMed literature search was conducted, followed by a manual search in recently published papers. Main criteria for selection were that patients had sustained a TBI, and that social cognition was the main target of treatment. A total of 16 papers and three reviews were selected and included in the present review. Results : Five studies (including three randomized controlled trials (RCT)) addressed facial affect recognition, one study specifically addressed emotional prosody, two RCTs used a combination of treatment strategies addressing social perception deficits. Six studies, including two RCTs, addressed social communication skills or theory of mind. Finally, two RCTs reported the effectiveness of a more global approach, addressing multiple domains of social cognition, such as emotion perception, social skills training, and theory of mind. Discussion/conclusion : Although there has been much less research on treatment of social cognition in patients with TBI as compared with psychiatric conditions, the findings reported in the present review are encouraging. Further multicenter large-scale RCTs are needed, with special emphasis on the generalization of treatment effects to social skills in everyday life.